Low Back Pain, Disability, and Quality of Life One Year following Intradiscal Injection of Autologous Bone Marrow Aspirate Concentrate - Colin M. Haines; Fenil R. Bhatt; Lindsay D. Orosz; Tarek Yamout; Samuel Namian; Niteesh Bharara; Anthony Bucci; Thomas C. Schuler; Ehsan Jazini; Christopher R. Good (Hindawi Limited, 2022)
Introduction. Degenerative disc disease is a common cause of chronic low back pain. Surgical intervention is an invasive treatment associated with high costs. There is growing interest in regenerative medicine as a less invasive but direct disc treatment for chronic discogenic low back pain. Objective. To evaluate clinical improvement of primary discogenic low back pain with intradiscal injection of autologous bone marrow aspirate concentrate (BMAC). Study Design. Prospective cohort study. Setting. Single, multiphysician center. Patients. 32 adult patients undergoing intradiscal injection of autologous BMAC for the treatment of primary discogenic low back pain. Interventions. Intradiscal injection of autologous BMAC. Main Outcome Measures. Primary outcome measure is visual analog back pain scale (VAS back pain). Secondary outcome measures include ODI, VAS leg pain, and EQ-5D-5L scores. Outcomes were compared from baseline to 1 year. Results. Thirty-two patients (56.3% male) with a mean age of 45.9 years were enrolled, giving 92 treated levels. Mean VAS back and leg pain scores improved from 5.4 to 3.0 (p<0.001) and 2.8 to 1.3 (p=0.005), respectively. Mean ODI scores decreased from 33.5 to 21.1 (p<0.001), and EQ-5D-5L scores improved from 0.69 to 0.78 (p=0.001). Using established MCID values, 59.4% had clinically significant improvement in VAS back pain, 43.8% in VAS leg pain, and 56.3% in ODI scores. Conclusion. Intradiscal injection of autologous BMAC significantly improved low back pain, disability, and quality of life at one year. This study suggests that intradiscal BMAC has the potential to be an effective nonsurgical treatment for chronic discogenic low back pain.